Buddhist scriptures as literature: sacred rhetoric and the uses of theory - Carmo Flores, Ralph Leonardo do (State University of New York Press, 2008)
Fictions of reading: Westerners and Buddhist texts -- A prince transformed: the Nikayas, the Nidanakatha -- Asvaghosa's Acts of the Buddha -- The Buddha awakening: the Nikayas -- Winning conversions: the Nikayas -- Passing on: the Nikayas -- Figures of right speech: the Dhammapada -- Joyous negations: the Heart sutra -- Masters of emptiness: the Gateless barrier and Zen folktales -- Extreme giving: the Vessantara jataka and -- Shantideva's a Guide to the bodhisattva way -- Final emergency reading: the Tibetan book of the dead -- Images in the reader